Public Participation and the Governance of Mineral Resources in Zimbabwe - Chikova, Rangarirai; Chilunjika, Alouis (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Public participation in policy issues by the locals is a crucial ingredient that guarantees the success of any policy decision, national project and public programme. Public participation should permeate every sphere of governance. In this vein, Zimbabwe is endowed with numerous mineral resources. The indigenous Zimbabwean are statutorily deemed as the owners of the mineral resources hence their participation in policy processes and spaces that relate to the governance of natural resources is pertinent. However, it was noted that the Zimbabwean population is not fully benefiting from the extraction of these mineral resources. The paper therefore explores the magnitude and essence of public participation in the governance of mineral resources in Zimbabwe. In achieving this, the paper is informed by Arnstein’s ladder of participation as the theoretical framework. In addition, data was gathered from documentary review and in-depth interviews with key informants. The study observed that public participation in respect of mineral governance can be undertaken through public hearing meetings, national budget consultative meetings and alternative mining indabas. However, the current level of participation is within the range of non-participation and lower tokenism. In addition, there is also lack of feedback and information flows in one direction from the Government officials to the citizens. The Government does not really take seriously the contributions from the public. The study therefore proffered some recommendations to enhance the levels of knowledge and participation by the public in the governance of mineral resources in Zimbabwe.